2020
DOI: 10.1101/2020.11.16.385740
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endothelial exosome plays functional role during rickettsial infection

Abstract: Spotted fever group rickettsioses (SFRs) are devastating human infections. Vascular endothelial cells (ECs) are the primary targets of infection. Edema resulting from EC barrier dysfunction occurs in the brain and lungs in most cases of lethal SFR, but the underlying mechanisms remain unclear. The aim of the study is to explore the potential role of Rickettsia (R)-infected, EC-derived exosomes (Exos) during infection. Using size-exclusion chromatography (SEC), we purified Exos from conditioned, filtered, bacte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(33 citation statements)
references
References 114 publications
(229 reference statements)
4
29
0
Order By: Relevance
“…Spotted fever group rickettsias are devastating human infections, and no licensed vaccine is available ( Liu et al, 2021 ). More than 20 species of Rickettsia are associated with SFGR, of which 16 are considered as human pathogens ( Cohen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spotted fever group rickettsias are devastating human infections, and no licensed vaccine is available ( Liu et al, 2021 ). More than 20 species of Rickettsia are associated with SFGR, of which 16 are considered as human pathogens ( Cohen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse brain microvascular endothelial cells (BMECs) were isolated from wild-type, EPAC1-KO, and ANXA2-KO mice using established protocol (1,8,19).…”
Section: Rickettsia and Cell Culturementioning
confidence: 99%
“…We recently unveiled a novel functional role played by EC-derived exosomes (ECExos) during rickettsial infection[26]. We validated that ECs efficiently take up exosomes (Exos) in vivo and in vitro [26]. We found that rickettsial-infected ECExos ( R -ECExos) induced disruption of the tight junctional (TJ) protein ZO-1 and barrier dysfunction of human normal recipient brain microvascular endothelial cells (BMECs) in a dose-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Exos contain many types of biomolecules[16] and convey signals to a large repertoire of recipient cells either locally or remotely by ferrying functional cargos, thus contributing to disease pathogenesis[20; 21; 22; 23; 24; 25]. We recently unveiled a novel functional role played by EC-derived exosomes (ECExos) during rickettsial infection[26]. We validated that ECs efficiently take up exosomes (Exos) in vivo and in vitro [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation